(untitled) (Journal Of Educational and Psychological Researches, 2019)
Abstract: The great expansion of teaching skills requires finding ways and methods to help teachers acquire experiences of all kinds. The researcher found in the subject of the teaching skills for teachers in public and private schools a fertile field for conducting a study that enables the measurement of these skills. Thus, the study aims to identify the skills of teaching lessons for teachers, the difference in teaching lesson skills for teachers according to the years of service, the differences in teaching lesson skills for teachers according to the specialized teachers and non-specialized teachers, the differences in teaching lesson skills for teachers according to the public and private school. The findings of research found that the teaching lesson skills are available in a medium degree of the most teachers. Additionally, years of experience have a significant role in the possession of the teacher to the teaching lesson skills, there is no difference observed in the teaching lesson skills between the specialized and non-specialized teachers, and there is no difference observed in teaching lesson skills for teachers in the public and private schools. Keywords: skill of presentation of the lesson, skills, methods of teachingArabic